2017
DOI: 10.1017/s1355617716000618
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Cognitive Mechanisms Underlying Pantomime of Tool Use: Evidence from Alzheimer’s Disease and Semantic Dementia

Abstract: Our results suggest that both functional and mechanical knowledge are important to pantomime the use of tools. To our knowledge, this is the first demonstration that mechanical knowledge plays a role in pantomime of tool use. Although impairment in pantomime of tool use tasks (i.e., apraxia) is widely explained by the disruption of manipulation knowledge, we propose that pantomime of tool use is a complex problem-solving task. (JINS, 2017, 23, 128-138).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…For instance, manipulation knowledge can be considered as a part of gesture engrams (kinematic components; Buxbaum et al, 2014) rather than on the same level. Finally, these two terms are used in the same manner in other studies(Jarry et al, 2016;Lesourd et al, 2017).…”
mentioning
confidence: 99%
“…For instance, manipulation knowledge can be considered as a part of gesture engrams (kinematic components; Buxbaum et al, 2014) rather than on the same level. Finally, these two terms are used in the same manner in other studies(Jarry et al, 2016;Lesourd et al, 2017).…”
mentioning
confidence: 99%
“…Indeed, the alternative tool selection and manipulation‐matching tasks were both selected as significant predictors and explained the same amount of variation as obtained in the PTU task. At first glance, this seems quite logical given that (1) the activation of manipulation knowledge is considered to be a prerequisite to pantomime the use of tools (e.g., Niessen, Fink, & Weiss, ); and that (2) it has recently been shown that mechanical knowledge is involved in pantomiming the use of tools (Baumard et al ., ; Lesourd, Baumard, Jarry, Etcharry‐Bouyx, et al ., ). However, regarding individual results in the pantomime production task, P12 and P19 had intriguing profiles.…”
Section: Discussionmentioning
confidence: 97%
“…We found a link between tasks assessing mechanical and manipulation knowledge (i.e., alternative tool selection and manipulation‐matching tasks) in both controls and in LBD patients, as already reported in other brain diseases (i.e., Alzheimer's disease and semantic dementia; Lesourd, Baumard, Jarry, Etcharry‐Bouyx, et al ., ). However, the link between mechanical and manipulation knowledge is still a matter of debate between the gesture engram and technical reasoning theories (for a discussion see Buxbaum, ; Osiurak & Badets, , ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this task, the examiner can only assess patients' motor actions, perhaps increasing the belief that the difficulty is necessarily due to a deficit for selecting the appropriate manipulation knowledge—and, as a result, a potential instance of loss of agency. However, evidence has shown that the demonstration by pantomime is a non-routine, creative task that can involve a plurality of cognitive processes (working memory, semantic memory, communicative skills, technical reasoning; Roy and Hall, 1992; Bartolo et al, 2003; Goldenberg et al, 2003; Baumard et al, 2014; Goldenberg, 2017; Lesourd et al, 2017; Finkel et al, 2018). This multi-determined nature of pantomime is also confirmed by the diversity of brain areas that can be involved in this task (left IPL, left temporal lobe; e.g., Goldenberg and Randerath, 2015; for review, see Niessen et al, 2014), whereas real tool use concerns mainly the left IPL (e.g., Goldenberg and Spatt, 2009).…”
Section: Selection Of Motor or Mechanical Actions?mentioning
confidence: 99%